2013
DOI: 10.1108/mhrj-03-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Online interactive suicide support services: quality and accessibility

Abstract: Purpose -Little research has focused on the quality and availability of interactive online support services retrieved through search engines. The purpose of this paper is twofold; first, to review and assess the availability and accessibility of interactive online support available to individuals in suicidal crisis. Second, to field test a new tool developed specifically to evaluate both the quality of online information and the quality of interactive support. Design/methodology/approach -A collection of six t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The literature highlights that individuals usually engage in informal help-seeking with friends and family, and formal helpseeking with professionals such as counsellors, health professionals and teachers. More recently, literature has described the use of technology such as online counselling, self-help apps and computerassisted programs (Best, Foye, Taylor, Hazlett and Manktelow, 2013).…”
Section: Help-seeking Behaviourmentioning
confidence: 99%
“…The literature highlights that individuals usually engage in informal help-seeking with friends and family, and formal helpseeking with professionals such as counsellors, health professionals and teachers. More recently, literature has described the use of technology such as online counselling, self-help apps and computerassisted programs (Best, Foye, Taylor, Hazlett and Manktelow, 2013).…”
Section: Help-seeking Behaviourmentioning
confidence: 99%
“…The researchers sought to replicate a search pattern similar to that of an individual wishing to access abortion services (therefore an individual who has made the decision to access abortion) using an established methodological approach 12 13. Data collection reflected our user-centred approach.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of this, we know relatively little of the mental well-being outcomes of online help-seeking. Best et al (2013, p. 2) note that online "support services may serve to reduce the potential emasculating consequences of stigmatising face-to-face help seeking, thus appealing to males in particular". This suggests that young males may favour this form of service yet in the same study the authors produced evidence suggesting a dearth of high quality online support.…”
Section: Figurementioning
confidence: 99%
“…In samples from 26 countries Cronbach's alpha's for this scale ranged from 0.76 -0.90 with the majority in the high 0.80s (Schwarzer and Jerusalem, 1995). services (Best et al, 2013) as no suitable tool could be identified for this domain.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation